Comparing aboveground primary production in areas of low and high nutrient levels in Mokré Louky, Třeboň Basin Biosphere Reserve - Káplová, Miroslava (Jihočeská univerzita, 2009)
Aboveground primary production differs depending on nutrient levels. This thesis compares net annual aboveground production and biomass levels in high and low areas of Mokré Louky. Aboveground plant biomass was collected from particular quadrats over two growing seasons, from April to September 2007 and April to October 2008. Samples were separated into species, dried and weighed.
Comparing aboveground primary production in areas of low and high nutrient levels in Mokré Louky, Třeboň Basin Biosphere Reserve
Keywords: wetlands; primary production; eutrophication; biomass; Mokré Louky; Phalaris arundinacea